Exploring the molecular mechanisms underlying head and neck cancer cachexia - Tavares, Patrícia da Silva (2020)
Head and neck cancer (HNC) is the sixth most common cancer worldwide, with estimated 630,000 new patients diagnosed annually, resulting in more than 350,000 deaths every year. Patients with HNC usually have large weight loss often associated with cachexia, a syndrome mainly characterized by muscle mass loss. Cachexia has been underdiagnosed in the set of HNC, resulting in increased rates of morbidity and impaired quality of life of patients. There are no effective therapeutic options for the management of this syndrome, which can be justified, at least in part, by its misdiagnosis. The objective of this dissertation was to characterize the body wasting phenotype of HNC patients and identify putative biomarkers to improve the early diagnosis and management of HNC cachexia. Thirty male patients were enrolled in this study and were assigned to one of two groups based on the nutritional risk index: HNC (NRI>97.5; n=16) or HNC+ cachexia (NRI<97.5; n=14). Targeted and nontargeted proteomic approaches were applied to the analysis of blood-derived serum and urine. Data highlighted the contribution of inflammation to the development of cachexia given by the high levels of C-reactive protein (CRP), IL-6 and TNF-α, which were associated to advanced stages of disease. The high circulating levels of myostatin seem to corroborate the occurrence of muscle wasting. The negative correlation observed between CRP and ghrelin suggests that HNC cachectic patients with CRP levels higher than 30 mg/dL may benefit from therapy with ghrelin agonists. Urine proteomics allowed the identification of 18 proteins modulated by cachexia, within the 520 distinct proteins identified by GeLC-MS/MS, such as alpha chain of C4-binding protein, CRP and argininosuccinate synthase, which emphasizes the contribution of inflammation to cachexia pathogenesis. Future studies will be important to validate the diagnosis value of these proteins for the management of cachexia in HNC and, eventually, in other types of cancer